EXPERIMENTAL CONFIRMATION OF THE EXACTNESS OF ORBITAL ARTIFICIAL NEAR EARTH OBJECTS "SICH-1" MEASURINGS WITH OPTICAL INSTRUMENTS BY ASTRONOMICAL OBSERVATORIES OF UKRAINE - Kirichenko, A. G.; Klimik, W. U.; Kudak, K. A. (Одеські астрономічні публікації, 2017)
In the article it is shown, that by photographic cameras AUF-75 with a consequent astrometric reduction of images artificial celestial bodies it is possible to make on observations from one item to calculate orbit of the satellite "Sich-1". A method to receive some orbit elements during the short time interval is present. Observations from three items will enable to update elements of orbit. The accuracy of calculation of orbits of the satellite makes up 10-20meters.